Transvaginal natural orifice specimen extraction surgery for left-sided colorectal resection: A single-centre cohort study - Ruben Gregory Xavier; Tao-Wei Ke; William Tzu-Liang Chen (Journal of Minimal Access Surgery)
Introduction: Transvaginal natural orifice specimen extraction surgery (NOSES) is an innovative and feasible approach for left-sided colorectal resections in females. This study aimed to report our experience with transvaginal NOSES for left-sided laparoscopic colorectal resections. Patients and Methods: We analysed data for all patients with transvaginal extraction performed for left-sided laparoscopic colorectal resections between 2011 and 2021 at a tertiary teaching hospital in Taiwan. Results: The 18 post-menopausal patients were of a mean age of 69.2 ± 10.14 years. The lesions were located at the descending (n = 5), sigmoid colon (n = 12) and rectum (n = 1). The operative time was 262.5 ± 83.91 min, and the blood loss was 34 ± 35.98 mL. All patients had an end-to-end anastomosis, and the anastomotic height was 15.06 ± 8.57 cm. Two patients received diversion stoma. The mean length of hospital stay was 5.1 days (standard deviation ± 2.42; range: 3–12 days). There were no cases of clinical infection. The pathology was malignancy (n = 14, 77.8%), diverticulitis (n = 2, 11.2%) and benign (n = 2, 11.2%). In cancers, they were Stage I (n = 1, 7.1%), IIa (n = 1, 7.1%), IIIb (n = 15, 78.7%) and IV (n = 1, 7.1%). Malignant specimens (n = 14) were mostly moderately differentiated (n = 11, 78.6%), with two poorly differentiated (14.3%) and one well-differentiated (7.1%). The lymph nodes harvested were 16.1 ± 8.11. The widest dimension of the lesion was 3.43 cm ± 1.28 (range: 1.5–6) and the length of the specimen was 14.69 cm ± 5.01 (range: 8–27). Conclusion: Transvaginal NOSES is safe and feasible for left-sided colorectal resection. Factors to consider are the characteristics of the specimen, anal canal and vagina.